2019
DOI: 10.24297/jbt.v8i0.8503
|View full text |Cite
|
Sign up to set email alerts
|

The Induction of High-Frequency Callus with an Elite Cotton (Gossypium Hirsutum L.) from Côte d'Ivoire

Abstract: In cotton, factors such as carbon sources, hormonal combination, and type of explant influence the responses to callus induction. In this study callus induction was optimized to get high-frequency callus in cotton. Different carbon sources were tested, and among them, glucose at 3% was found to be the best carbohydrate in callus induction. Culture medium supplemented with 2,4-D (0.1 mg.L-1) and KIN (0.5 mg.L-1) gave a high callogenesis response, unlike other hormonal combinations. With explants, hypocotyl (72.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 15 publications
0
0
0
Order By: Relevance
“…This phenolic compound, 3pcoumaric acid, is synthesised through the tyrosine pathway. In contrast, in control plants, these authors [24] showed a predominance of hydroxycinnamic acid, flavonoids (catechin and gossypetin), resveratrol and pterostilbene. PAL, with a participation rate of 62.05 %, was responsible for the synthesis of these compounds in the control plants.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…This phenolic compound, 3pcoumaric acid, is synthesised through the tyrosine pathway. In contrast, in control plants, these authors [24] showed a predominance of hydroxycinnamic acid, flavonoids (catechin and gossypetin), resveratrol and pterostilbene. PAL, with a participation rate of 62.05 %, was responsible for the synthesis of these compounds in the control plants.…”
Section: Discussionmentioning
confidence: 78%
“…As these enzymes are biosynthetic enzymes, their high activity in the treated plants suggests that FOS stimulates the biosynthesis of phenolic compounds. Indeed, N'goran et al [24] showed that FOS from Fusarium oxysporum f. sp. Vasinfectum (FOV) stimulated the production of phenolic compounds in cotton.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation